Fiscal Consolidation in Southeastern European Countries : The Role of Budget Institutions - Olden, Brian (IMF Working Papers; Working Paper, 2012)
This paper assesses the relative strengths and weaknesses of fiscal institutions in ten Southeastern European countries, using recent benchmarking methodologies developed by FAD. The assessment evaluates each country's understanding of the scale of the fiscal adjustment challenge, its ability to develop a credible consolidation strategy, and its capacity to implement the strategy. Key institutional arrangements, are generally in place, including top-down budgeting and medium-term budget frameworks. Other institutional arrangements require further attention, including macro-fiscal forecasting, fiscal risk analysis, setting fiscal objectives, presence and role of independent fiscal agencies, and top-down parliamentary approval.